PEMBERDAYAAN MASYARAKAT DESA KONDA MALOBA MENUJU DESA WIRAUSAHA MANDIRI - Nau, Rinto Tay Ratu; Rihi, Frisky Raja; Lunga, Jesi Tenga; Adung, Yules Retang Hugu; Hawur, Bertha Karanja; Banju, R. Adinda Hamba; Lede, Floris Irnanda; Dairu, Elmiana R. Sedu; Pura, Fader Umbu; Berlian, Verlin; Danga, Neplin Yaku; Amah, Emilia Ana; Henggu, Krisman Umbu (ABDI WINA JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
The Independent Entrepreneurial Village concept is a key aspect of the strategy to accelerate economic growth in rural areas. Such villages are distinguished by their community's capability to manage natural resources through entrepreneurial initiatives. The goal of implementing the Mandiri Entrepreneurial Village Thematic KKN is to empower the Konda Maloba Village community by providing training and mentoring in areas such as agriculture, animal husbandry, fisheries, and educational services, particularly in literacy and numeracy for early childhood and elementary school levels. The KKN initiative begins with delivering educational materials and conducting a problem analysis in Konda Maloba Village utilizing the Project Action Plan (PAP) approach. The outcomes of this analysis serve as the foundation for designing the KKN program. Implementation occurs through socialization, training, and mentorship sessions. The KKN activities in Konda Maloba Village involve creating natural pesticides, software development, editing training, establishing early childhood learning centers, producing smoked fish, and conducting various incidental programs. All activities are tailored to meet the village's needs and actively engage the community throughout the process.